Inscripción de la promesa de compraventa de bienes inmuebles y el principio de publicidad - Lascano Frías, Carlos Milton (2025)
This research analyzes the relevance of the registration of the promise of sale of real estate in the Property Registry, highlighting how the omission of this registration act may violate the principle of publicity. Although Ecuadorian law does not establish the obligation to register this type of agreement, it is argued that the lack of visibility in the registry generates uncertainty, regarding the ownership of the rights over the property, which may lead to situations of fraud or legal conflicts. The main objective of the research was to analyze the possible violation of the principle of publicity due to lack of registration of the promise of sale of real estate in the land registry. A descriptive documentary methodology with a qualitative approach was used, through interviews with notaries and lawyers, as well as the analysis of legislation and doctrine. The results revealed that, although formalization by means of a public deed is a sufficient regulatory requirement, registration provides greater protection to the parties involved and interested third parties. In addition, it was found that the lack of registration violates the principle of publicity, limiting access to information that is crucial for decision - making. In conclusion, legislative reform was recommended to make the registration of the promise of purchase and sale mandatory, in order to strengthen transparency, publicity, legal certainty and the protection of the rights of the parties involved in these transactions.